Cell Type–Specific Contributions of the Angiotensin II Type 1a Receptor to Aorta Homeostasis and Aneurysmal Disease—Brief Report. Issue 3 (March 2018) - Galatioto, Josephine; Caescu, Cristina I.; Hansen, Jens; Cook, Jason R.; Miramontes, Irving; Iyengar, Ravi; Ramirez, Francesco
Abstract : Objective—: Two were the aims of this study: first, to translate whole-genome expression profiles into computational predictions of functional associations between signaling pathways that regulate aorta homeostasis and the activity of angiotensin II type 1a receptor (At1ar) in either vascular endothelial or smooth muscle cells; and second, to characterize the impact of endothelial cell– or smooth muscle cell–specific At1ar disruption on the development of thoracic aortic aneurysm in fibrillin-1 hypomorphic ( Fbn1 mgR/mgR ) mice, a validated animal model of early onset progressively severe Marfan syndrome. Approach and Results—: Cdh5-Cre and Sm22-Cre transgenic mice were used to inactivate the At1ar-coding gene ( Agt1ar ) in either intimal or medial cells of both wild type and Marfan syndrome mice, respectively. Computational analyses of differentially expressed genes predicted dysregulated signaling pathways of cell survival and matrix remodeling in Agt1ar Cdh5 −/− aortas and of cell adhesion and contractility in Agt1ar Sm22 −/− aortas. Characterization of Fbn1 mgR/mgR ;Agt1ar Cdh5 −/− mice revealed increased median survival associated with mitigated aneurysm growth and media degeneration, as well as reduced levels of phosphorylated (p-) Erk1/2 but not p-Smad2. By contrast, levels of both p-Erk1/2 and p-Smad2 proteins were normalized in Fbn1 mgR/mgR ;Agt1ar Sm22 −/− aortas in spite of them showing no appreciable changes in thoracic aortic aneurysm pathology. Conclusions—: Physiological At1ar signaling in the intimal and medial layers is associated with distinct regulatory processes of aorta homeostasis and function; improper At1ar activity in the vascular endothelium is a significant determinant of thoracic aortic aneurysm development in Marfan syndrome mice. Abstract : Supplemental Digital Content is available in the text.